FRI0357 Validation of a disease-specific health – related quality of life measure for russian adult patients with systemic lupus erythematosus: lupusqol-russian. (12th June 2018) - Aseeva, E.; Vorobyova, L.; Soloviev, S.; Koilubaeva, G.; Glukhova, S.
Abstract : Background: Improvements in the survival of patients with systemic lupus erythematosus (SLE) in Russia have to some extent paralleled that seen worldwide over the last 20 years, but have at times come at the cost of increased morbidity and reduction in health-related quality of Life (HRQol). Recently, a specific questionnaire to evaluate HRQol in adult SLE patients (LupusQoL) has been developed and validated in United Kingdom and in several European countries. Objectives: To assess the validity of a LupusQoL-Russian in adult SLE patients Methods: The LupusQoL-Russian was administered to a cohort of russian patients affected with SLE. To perform a control, QoL was evaluated also with SF-36. The Russian version of LupusQoL questionnaire was developed by the University of Central Lancashire and the East Lancashire Hospitals NHS Trust (www.lupusqol.com), after a linguistic validation process. Disease activity was evaluated by the SLEDAI-2K, and chronic damage by the Systemic Lupus International Collaborating Clinics Damage Index score (SDI). Internal consistency and test-retest reliability, convergent and discriminant validity were examined. Results: 328 Russian SLE patients were enrolled in the study (M/F 30/298, mean age 34, 4±11.5 years, mean disease duration 106.3±97.9 months; mean SLEDAI 2K 9, 6±8, 0; mean SDI 0.2±0.6). The LupusQoL-Russian demonstrated substantial evidence of construct validity. Each domain showed good correlation when compared with equivalent domains of the SF-36 (p<0.001 for all comparisons). LupusQoL-Russian discriminated between patients with different degrees of disease activity according to SLEDAI 2K: Lupus-QoL domains showed a trend to lower values in patients with higher disease activity (SLEDAI-2K≥4) compared with those with lower disease activity (SLEDAI 2K<4), reaching statistically significant difference when considering the domains "Pain", "Planning'', Intimate relationship"and ''Body image» (p=0.007, p=0.0004, p=0003 and p=0, 007, respectively). LupusQol-Russian was significantly lower for ``Physical health'', "Planning" and "Fatigue" in patients with SDI≥1 (p=0.002, p=0.03, and p=0, 03) respectively (table 1). Test-retest reliability was good to excellent between baseline and day 3 (intraclass correlation coefficient (ICC) 0.7–0.9) Conclusions: The LupusQoL-Russian is valid to assess quality of life in SLE patients Disclosure of Interest: None declared